Right-width cuffs – survey on a specific group of children and teenagers - Chaves, Emília Soares; Guedes, Nirla Gomes; Moreira, Rafaella Pessoa; Cavalcante, Tahissa Frota; Lima, Rhanna Emanuela Fontenele; Araújo, Thelma Leite de (Rev Rene, 2004)
The objective of this study was to investigate the width of cuffs that would be more adequate for the measuring of arterial pressure of children and teenagers, taking into account the proportion recommended, which means 40% of the circumference of the arm. This study was carried out in Fortaleza and involved 166 children and teenagers from both sexes between 6 and 18 years old. Most of them were females (53%). The circumference of their arms varied from 14 to 49cm. The most adequate sizes of cuffs were of 8, 9 and 10cm. The 8cm-cuff was predominant in all ages. It was possible to conclude that it is important to reinforce the importance of adopting as a criterion for the right choice of cuffs, particulary for children and teenagers, the measure of the circumference of the arm and not the chronological age.